COMPARATIVE ANALYSIS OF THE QUALITY OF E-KTP MAKING SERVICES IN CISAUK DISTRICT, TANGERANG REGENCY AND CIPUTAT TIMUR DISTRICT, TANGERANG SELATAN CITY - Putri Cahyani, Lisa; Yulyana, Eka (INDONESIAN JOURNAL OF SOCIAL POLITIC AND POLICY STUDIES, 2024)
The Cisauk District Office and East Ciputat District Office are extensions of the Disdukcapil to help meet the needs of the local community, especially in the service of making Resident Identity Cards (KTP). The aim of this research is to determine and analyze the comparison of the quality of services for making electronic Identity Cards (e-KTP) in Cisauk District, Tangerang Regency and East Ciputat District, South Tangerang City. In this research, researchers used the service quality theory from Zeithaml et.al which refers to 5 dimensions, namely direct evidence (tangible), reliability, responsiveness, assurance and empathy. This research uses a qualitative descriptive research design using primary and secondary data collection techniques by conducting interviews, literature studies and observations. Interviews were conducted with service staff and the community as service recipients. The research results show that the quality of e-KTP making services in Cisauk District and East Ciputat District based on the theory used is quite good. However, there are still problems such as servers suddenly having problems, this can hamper the e-KTP service process.